High-strength cross-linked polymer gel plugging agent as well as preparation and use methods thereof

By using high-strength crosslinked polymer gel plug-in regulator in oil and water wells, the gel strength is enhanced by using the crosslinked network structure, the problem of the deterioration of the existing plug-in regulator in water flooding is solved, and the high-quality effect is achieved Effective sealing and water erosion resistance of the permeable area reduce the cost of reservoir development.

CN119286486APending Publication Date: 2025-01-10TANGSHAN JIYOU RUIFENG CHEM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411444013.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The effect of existing oil and water well blocking agents gradually deteriorates during the water flooding process, especially the lack of interaction between pre-crosslinked particles and cross-linked polyacrylamide, resulting in a reduction in the sealing strength, and multiple rounds of blocking are required to be frequently performed. Increased reservoir development costs.

Method used

Using high-strength crosslinked polymer gel plugging agent, the crosslinking network structure is formed to enhance the strength of the gel by adding silicon modified polyacrylamide gel particles, phenolic resin, anhydrous ethanol and oxalic acid to the polyacrylamide. and stability, suitable for oil reservoirs with medium and high temperatures and large permeability differences.

Benefits of technology

Effective sealing of high permeability areas under medium and high temperature environments is achieved, the water erosion and sealing rate of the plug-in regulator is improved, the reduction of the sealing rate during subsequent water flooding is reduced, and the reservoir development cost is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-strength cross-linked polymer gel profile control agent and a preparation and use method thereof, and the profile control agent comprises the following components by mass: 0.2-0.5% of polyacrylamide; 1 to 5 percent of silicon modified polyacrylamide gel particles; 0.12 to 0.3% of phenolic resin; 0.24 to 0.6 percent of absolute ethyl alcohol; 0.05 to 0.2 percent of oxalic acid; and the balance of water. Compared with the prior art, the plugging agent disclosed by the invention can be used for oil reservoirs with medium-high temperature of 80-120 DEG C, large permeability difference and large pore or crack development. The silicon-modified polyacrylamide gel particles can be subjected to a cross-linking reaction with polyacrylamide of a macromolecular chain structure, the polyacrylamide is self-crosslinked at the same time, and finally the silicon-modified polyacrylamide gel particles are crosslinked and fixed in a polyacrylamide cross-linked network structure to form an integrated cross-linked structure, so that the strength is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and water well plugging agents, and in particular to a high-strength cross-linked polymer gel plugging agent and a preparation and use method thereof. Background Art

[0002] In the middle and late stages of oilfield development, with continuous strong injection and strong production, the heterogeneity of the reservoir will generally increase, the permeability difference will increase, and the high permeability zone will further develop into a large pore, which will reduce the effect of water injection and polymer injection or cause water flooding or polymer channeling in the oil well. In order to improve the effect of water injection and chemical flooding and increase the utilization of reserves in low permeability areas, water well profile control and oil well water plugging have become very important measures.

[0003] Among the many plugging agents for oil and water wells in oil fields, polyacrylamide plugging agents are favored by oil fields because of their relatively low price, simple construction process, strong adaptability and low risk. They are used in the largest amount among various plugging agents. They mainly exist in the form of cross-linked polyacrylamide gels that play a "surface" plugging role and pre-cross-linked polyacrylamide particles that play a "point" plugging role in the pores. When plugging high-permeability reservoirs in formations, the composite form of the two is generally used. In the early stage of water flooding, it can play an obvious plugging effect, but as the water flooding progresses, the effect gradually deteriorates and even fails. The main reason is that there is no interaction between the pre-cross-linked particles and the cross-linked polyacrylamide, and the drag force between them is weak or non-existent. In the long-term water flooding process, the cross-linked polymer that plays a "surface" plugging gradually moves under the water injection pressure or gradually separates from the gel particles that play a "point" plugging in other ways, reducing the overall plugging strength. Therefore, oil fields generally use multiple rounds of plugging methods to maintain the development of reservoirs, which increases the development cost of reservoirs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-strength cross-linked polymer gel plugging agent and a preparation and use method thereof.

[0005] To achieve this technical purpose, the present invention adopts the following scheme: In a first aspect, a high-strength cross-linked polymer gel plugging agent includes the following components in mass percentage: polyacrylamide, 0.2-0.5%; silicon-modified polyacrylamide gel particles, 1-5%; phenolic resin, 0.12-0.3%; anhydrous ethanol, 0.24-0.6%; oxalic acid, 0.05-0.2%; and the rest is water.

[0006] A preferred solution is: polyacrylamide accounts for 0.2%; silicon-modified polyacrylamide gel particles account for 1%; phenolic resin accounts for 0.12%; anhydrous ethanol accounts for 0.24%; oxalic acid accounts for 0.05%; and water accounts for 98.39%.

[0007] Another preferred solution is: polyacrylamide accounts for 0.35%; silicon-modified polyacrylamide gel particles account for 3%; phenolic resin accounts for 0.21%; anhydrous ethanol accounts for 0.42%; oxalic acid accounts for 0.1%; and water accounts for 95.92%.

[0008] Another preferred solution is: polyacrylamide accounts for 0.5%; silicon-modified polyacrylamide gel particles account for 5%; phenolic resin accounts for 0.3%; anhydrous ethanol accounts for 0.6%; oxalic acid accounts for 0.2%; and water accounts for 93.4%.

[0009] Secondly, a method for preparing a high-strength cross-linked polymer gel plugging agent is provided, which comprises adding water into a container, turning on a stirring device, adding polyacrylamide, and ripening for 10 to 15 minutes, and then sequentially adding silicon-modified polyacrylamide gel particles, phenolic resin, anhydrous ethanol, and oxalic acid, stirring each material for 5 to 10 minutes. After all materials are added, stirring is continued for 10 to 15 minutes to obtain a high-strength cross-linked polymer gel plugging agent.

[0010] The preparation method of silicon-modified polyacrylamide gel particles is as follows: add water into a container, turn on the stirring device, add 0.3% acrylamide, and then add 0.15% phenolic resin, 0.05% oxalic acid, and 2% silicone in sequence, stirring each time a material is added for 5 to 10 minutes. After all are added, continue stirring for 10 to 15 minutes to obtain silicon-modified polyacrylamide gel particles.

[0011] A preferred solution is: to 50 g of a 0.4% by mass polyacrylamide aqueous solution, 1 g of silicon-modified polyacrylamide gel particles, 0.12 g of phenolic resin, and 0.24 g of anhydrous ethanol are added in sequence while stirring, and each material is stirred for 5 minutes. Finally, 0.05 g of oxalic acid and the remainder of water are mixed to form an oxalic acid solution, and then added, and stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent.

[0012] Another preferred solution is: in 70g of a 0.5% by mass polyacrylamide aqueous solution, 3g of silicon-modified polyacrylamide gel particles, 0.21g of phenolic resin, and 0.42g of anhydrous ethanol are added in sequence while stirring, and each material is stirred for 5 minutes. Finally, 0.1g of oxalic acid and the remainder of water are mixed to form an oxalic acid solution, and then added, and stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent.

[0013] Another preferred scheme is: in 83.3g of 0.6% polyacrylamide aqueous solution by mass, 5g of silicon-modified polyacrylamide gel particles, 0.3g of phenolic resin, and 0.6g of anhydrous ethanol are added in sequence while stirring, and each material is stirred for 5 minutes. Finally, 0.2g of oxalic acid and the remainder of water are mixed to form an oxalic acid solution, and then added, and stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent.

[0014] Thirdly, the method for using the high-strength cross-linked polymer gel plugging agent is to maintain the high-strength cross-linked polymer gel plugging agent at a constant temperature of 80 to 120°C for a gel time of 13 to 76 hours, and the system forms a semi-fluid or non-fluid high-strength gel in which the particles and the cross-linked polyacrylamide are cross-linked and integrated.

[0015] A preferred solution is that the high-strength cross-linked polymer gel plugging agent is used at an ambient temperature of 80° C., and the gel time is 28 to 76 hours.

[0016] Another preferred solution is that the high-strength cross-linked polymer gel plugging agent is used at an ambient temperature of 95° C., and the gel time is 21 to 49 hours.

[0017] Another preferred solution is that the high-strength cross-linked polymer gel plugging agent is used at an ambient temperature of 120° C., and the gel time is 13 to 27 hours.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The plugging agent of the present invention can be used in medium-high temperature of 80-120°C, oil reservoirs with large permeability differences, large pores or developed fractures. The silicon-modified polyacrylamide gel particles can undergo a cross-linking reaction with the polyacrylamide of the polymer chain structure, and the polyacrylamide is self-cross-linked at the same time, and finally the silicon-modified polyacrylamide gel particles are cross-linked and fixed in the cross-linked network structure of the polyacrylamide to form an integrated cross-linked structure with higher strength. DETAILED DESCRIPTION

[0019] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific implementation methods, but the present invention is not limited thereto.

[0020] The raw materials used in the embodiments of the present invention are as follows: Polyacrylamide: white powdery solid, hydrolysis degree 10%, molecular weight 8 million, quickly soluble in water, and can be cross-linked with a cross-linking agent to form an insoluble gel. Raw material provider: Aisen (China) Flocculant Co., Ltd. Silicon modified polyacrylamide gel particles: polyacrylamide pre-crosslinked gel particles synthesized from silicone, acrylamide and other additives, which absorb water and swell slowly. Raw material provider: Drilling and Production Technology Experiment Center of Jidong Oilfield Branch; The preparation method of silicon-modified polyacrylamide gel particles is as follows: add water into a container, turn on the stirring device, add 0.3% acrylamide, and then add 0.15% phenolic resin, 0.05% oxalic acid, and 2% silicone in sequence, stirring each time a material is added for 5 to 10 minutes. After all are added, continue stirring for 10 to 15 minutes to obtain silicon-modified polyacrylamide gel particles.

[0021] Phenolic resin: a cross-linking agent for polyacrylamide, which can improve the stability of the gel and extend the freezing time; raw material provider: Hebei Jidong Oilfield Ruifeng Chemical Co., Ltd.

[0022] Anhydrous ethanol: a colorless, easy-flowing liquid. It is volatile and has an alcohol smell. Substances that are difficult to dissolve or insoluble in water, such as iodine, camphor, rosin or pigments, can be dissolved by ethanol. Raw material provider: Hebei Jidong Oilfield Ruifeng Chemical Co., Ltd. Oxalic acid: oxalic acid, structural formula HOOCCOOH, pH value regulator. Raw material provider: Hebei Jidong Oilfield Ruifeng Chemical Co., Ltd. Example 1

[0023] Preparation of silicon-modified polyacrylamide gel particles: Add 100 ml of water into a container, turn on the stirring device, add 0.3 g of acrylamide, and then add 0.15 g of phenolic resin, 0.05 g of oxalic acid, and 2 g of silicone in sequence. Stir for 5 to 10 minutes each time each material is added. After all are added, continue stirring for 10 to 15 minutes to obtain silicon-modified polyacrylamide gel particles.

[0024] In 50g of 0.4% polyacrylamide aqueous solution, 1g of silicon-modified polyacrylamide gel particles, 0.12g of phenolic resin, and 0.24g of anhydrous ethanol were added in sequence while stirring. Each material was stirred for 5 minutes. Finally, 0.2g of oxalic acid and the remaining water were mixed to form an oxalic acid solution, and then stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent. Its components are (by mass ratio): 0.2% polyacrylamide + 1% silicon-modified polyacrylamide gel particles + 0.12% phenolic resin + 0.24% anhydrous ethanol + 0.05% oxalic acid + 98.39% water. The gel time of this system is 76h at 80℃, 39h at 95℃, and 27h at 120℃. Example 2

[0025] In 70g of 0.5% polyacrylamide aqueous solution, 3g of silicon-modified polyacrylamide gel particles, 0.21g of phenolic resin, and 0.42g of anhydrous ethanol were added in sequence while stirring. Each material was stirred for 5 minutes. Finally, 0.1g of oxalic acid and the remaining water were mixed to form an oxalic acid solution, and then stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent. Its components are (by mass ratio): 0.35% polyacrylamide + 3% silicon-modified polyacrylamide gel particles + 0.21% phenolic resin + 0.42% anhydrous ethanol + 0.1% oxalic acid + 95.92% water. The gel time of this system is 59h at 80℃, 41h at 95℃, and 22h at 120℃. Example 3

[0026] In 83.3g of polyacrylamide aqueous solution with a mass fraction of 0.6%, 5g of silicon-modified polyacrylamide gel particles, 0.3g of phenolic resin, and 0.6g of anhydrous ethanol were added in sequence while stirring. Each material was stirred for 5 minutes. Finally, 0.2g of oxalic acid and the remaining water were mixed to form an oxalic acid solution, and then stirred for 10 minutes to form a high-strength cross-linked polymer gel plugging agent. Its components are (by mass ratio): 0.5% polyacrylamide + 5% silicon-modified polyacrylamide gel particles + 0.3% phenolic resin + 0.6% anhydrous ethanol + 0.2% oxalic acid + 93.4% water. The gel time of this system is 28h at 80℃, 21h at 95℃, and 13h at 120℃.

[0027] Comparative Example 1 Compared with Example 3, without adding silicon-modified polyacrylamide gel particles, the gel time of the system at 80°C was 25 h, the gel time at 95°C was 16 h, and the gel time at 120°C was 10 h.

[0028] Comparative Example 2 Compared with Example 3, without adding the polyacrylamide aqueous solution, the gel time of the system at 80° C. was 19 h, the gel time at 95° C. was 12 h, and the gel time at 120° C. was 6 h.

[0029] Comparative Example 3 Compared with Example 3, the silicon-modified polyacrylamide gel particles were replaced by polyacrylamide gel particles. The gel time of the system was 26 h at 80° C., 18 h at 95° C., and 12 h at 120° C.

[0030] The high-strength cross-linked polymer gel plugging agent prepared in Example 3 was used to conduct a physical simulation experiment. The initial water permeability was 1.302 μm 2 、2.506μm 2 and 3.541 μm 2 0.3PV high-strength cross-linked polymer gel plugging agent was squeezed into the cores. The three cores were cured at 120°C for 24 hours to ensure that the plugging agent was gelled. The water permeability was 3.12×10 -3 μm 2 , 6.67×10 -3 μm 2 and 57.31×10 -3 μm 2 , the corresponding plugging rates were 99.76%, 99.73% and 98.38%. After the subsequent water flooding of 15PV, the plugging rate decreased by 0.76-3.18%. This shows that the high-strength cross-linked polymer gel plugging agent has excellent plugging ability and water scouring resistance for high permeability bands after gelation, and is suitable for profile control and water plugging work, especially for profile control and water plugging work in medium and high permeability reservoirs.

[0031] The high-strength cross-linked polymer gel plugging agent prepared in Comparative Example 1 was used to conduct a physical simulation experiment. The initial water permeability was 1.302 μm 2 、2.506μm 2 and 3.541 μm 2 0.3PV high-strength cross-linked polymer gel plugging agent was squeezed into the cores. The three cores were cured at 120°C for 24 hours to ensure that the plugging agent was gelled. The water permeability was 6.35×10 -3 μm 2 , 11.88×10 -3 μm 2 and 202.19×10 -3 μm 2 The corresponding plugging rates were 95.12%, 95.26% and 94.29%. After the subsequent water flooding of 15 PV, the plugging rate decreased by 8.89-11.54%.

[0032] Finally, it should be noted that the above are only preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the scope of protection of the present invention.

Claims

1. A high-strength cross-linked polymer gel plugging agent, characterized in that: The invention comprises the following components in mass percentage: polyacrylamide, 0.2-0.5%; silicon-modified polyacrylamide gel particles, 1-5%; phenolic resin, 0.12-0.3%; Anhydrous ethanol, 0.24-0.6%; oxalic acid, 0.05-0.2%; the rest is water.

2. The high-strength cross-linked polymer gel plugging agent according to claim 1, characterized in that: Polyacrylamide accounts for 0.2%; silicon-modified polyacrylamide gel particles account for 1%; phenolic resin accounts for 0.12%; anhydrous ethanol accounts for 0.24%; oxalic acid accounts for 0.05%; and water accounts for 98.39%.

3. The high-strength cross-linked polymer gel plugging agent according to claim 1, characterized in that: Polyacrylamide accounts for 0.35%; silicon-modified polyacrylamide gel particles account for 3%; phenolic resin accounts for 0.21%; anhydrous ethanol accounts for 0.42%; oxalic acid accounts for 0.1%; and water accounts for 95.92%.

4. The high-strength cross-linked polymer gel plugging agent according to claim 1, characterized in that: Polyacrylamide accounts for 0.5%; silicon-modified polyacrylamide gel particles account for 5%; phenolic resin accounts for 0.3%; anhydrous ethanol accounts for 0.6%; oxalic acid accounts for 0.2%; and water accounts for 93.4%.

5. The method for preparing the high-strength cross-linked polymer gel plugging agent according to any one of claims 1 to 4, characterized in that: Add water into the container, turn on the stirring device, add polyacrylamide, mature for 10 to 15 minutes, then add silicon-modified polyacrylamide gel particles, phenolic resin, anhydrous ethanol and oxalic acid in sequence, stir for 5 to 10 minutes each time each material is added, and after all are added, continue stirring for 10 to 15 minutes to obtain a high-strength cross-linked polymer gel plugging agent.

6. The method for preparing the high-strength cross-linked polymer gel plugging agent according to claim 5, characterized in that: The preparation method of silicon-modified polyacrylamide gel particles is as follows: add water into a container, turn on the stirring device, add 0.3% acrylamide, and then add 0.15% phenolic resin, 0.05% oxalic acid, and 2% silicone in sequence, stirring each time a material is added for 5 to 10 minutes. After all are added, continue stirring for 10 to 15 minutes to obtain silicon-modified polyacrylamide gel particles.

7. The method for using the high-strength cross-linked polymer gel plugging agent according to any one of claims 1 to 4, characterized in that: The high-strength cross-linked polymer gel plugging agent is maintained at a constant temperature of 80 to 120° C., and the gel time is 13 to 76 hours.

Citation Information

Cited By

  • Salt-sensitive viscoelastic gel modifying and flooding agent and preparation method thereof

    CN120555042A

  • Salt-sensitive viscoelastic gel profile control agent and preparation method thereof

    CN120555042B